A multifunctional nanostructured molybdenum disulphide (MoS2): an overview on synthesis, structural features, and potential applications. (16th April 2023) - Vidya, C.; Manjunatha, C.; Pranjal, A.; Faraaz, I.; Prashantha, K.
ABSTRACT: Molybdenum disulphide (MoS2 ) is a versatile inorganic material due to its unique electronic, electrical, optical, and biological properties, hence widely studied for various engineering applications. The main objective of this review is to provide comprehensive information about MoS2 for the researcher intended to start research on MoS2 . The beginning of the review is focused on providing information on the methods, precursors, and conditions used for the synthesis of various MoS2 nanostructures such as nanospheres, nanotubes, nanoflakes, nanobelts, nanoflowers, nanofibers, nanoclusters, nanosheets, and nanowires. The structural features of MoS2, both in pure and with other composite forms, are discussed in detail using the XRD, Raman, PL and UV–visible spectra reported by various research groups. Further, the detailed morphological features of both pure and composite forms of MoS2 are also discussed by taking selected works of SEM and TEM images. Finally and very importantly, the review also summarises the multifunctional applications of the versatile MoS2 and its composites in lubricants, exploring its tribological properties, in lithium-ion batteries, revealing its electrical and electronic property, as a catalyst for water splitting hydrogen evolution reaction, oxygen evolution reactions, endorsing its potential electrochemical property, various biomedical applications such as bio sensors, bioimaging, and very importantly in environmental applications. Graphical Abstract: Schematic illustration of the Application of MoS2 Graphical Abstract is Reproduced with permission from [1 ] [2 ], [3 ]: uf0001 Graphical Abstract is Reproduced with permission from [1 ] [2 ], [3 ].